PEMODELAN ARIMA-GARCH UNTUK VOLATILIAS DAN VALUE AT RISK PADA SAHAM PT. GUDANG GARAM TBK - Rosi Ramayanti; Dodi Devianto; Delvia Alhusna (LPPM Universitas Bina Bangsa, 2023)
Investment is one of the development factors in economic activity, there are two basic things that investor must know before making investment decisions, namely: returns and risk. One of the statistical methods to calculate the maximum loss in investment is Value at Risk (VaR). this study aims to calculate VaR on the closing stock price data of Pt. Gudang Garam TBK for the daily period starting from 4 January 2021 to 30 December 2021. Log return data is model by ARIMA. The ARIMA model contains a heteroscedasticity effect so it is inadequate for modelling, one of the models that can overcome the heteroscedasticity problem is the ARCH-GARCH model. Forecasting the volatility of the data is done using the ARCH-GARCH model. The results show that the GARCH (1,1) is the best model for predicting volatility. Volatility is predicted for the next 30 days, after the volatility forecasting results are obtained, the VaR calculation can be continued. Based on the results, it shows that volatility increases over time, which means that the risk that investor will accept will be higher and the returns will also be greater